The genome of a new anemone species (Actiniaria: Hormathiidae) provides insights into deep-sea adaptation. (April 2021) - Feng, Chenguang; Liu, Ruoyu; Xu, Wenjie; Zhou, Yang; Zhu, Chenglong; Liu, Jun; Wu, Baosheng; Li, Yongxin; Qiu, Qiang; He, Shunping; Wang, Wen; Zhang, Haibin; et al.
Abstract: Deep-sea (deeper than 200 m) creatures are poorly understood taxa that live in high-pressure, dark, and cold environments. Here, we provide a high-quality genome assembly of a new deep-sea anemone species ( Paraphelliactis xishaensis sp. nov.) living at a depth of 3230 m in the Xisha Trough in the South China Sea. Through comparative genomic analyses, we revealed molecular signatures of deep-sea environment adaptation including the rapid evolution of genes involved in cytoprotective osmolyte metabolism, membrane function, translational activity, and cytoskeletal processes in deep-sea anemone, along with parallel amino acid substitutions in genes between the deep-sea anemone and deep-sea mussel to cope with high hydrostatic pressure or low temperature. Finally, the inferred demographic events of this deep-sea anemone coincide with major post-Pliocene climate transformations, implying that global climate changes also affect creatures in deep-sea zones. Together, these results extend our understanding of the adaptation and evolutionary history of deep-sea creatures. Highlights: A new deep-sea anemone species was described and named. The genome of the new deep-sea anemone species was provided. Molecular signatures of deep-sea environment adaptation were detected from the genome. Response signatures to global environmental changes were detected in the anemone's inferred demographic history.